A Novel Supraretinacular Endoscopic Carpal Tunnel Release: Instrumentation and Technique (Cadaveric Study) - Teh, Kok Kheng; Choo, Ch'ng Hwei; Shanmugam, Rukmanikanthan; Ngim, Joanne Hui-ling; Ahmad, Tunku Sara (Elsevier, 2019)
Purpose: Endoscopic carpal tunnel release has been shown to be associated with a shorter return to work compared with open carpal tunnel release in the treatment of carpal tunnel syndrome. Unfortunately, it may be associated with a higher risk for median nerve injury when the carpal tunnel is used as a portal for instrumentation. The purpose of this study was to assess safety in using a newly designed retractor through a supraretinacular approach. Methods: We used 8 wrists (4 left and 4 right wrists) from 4 fresh-frozen cadavers for this study. Supraretinacular endoscopic carpal tunnel release using the supraretinacular retractor was performed by a single investigator, followed by exploration of the carpal tunnel and the structures surrounding it. Surgeries were performed using a new surgical instrument consisting of an arch-shaped blade and handle. It includes a retainer adapted to receive a 2.4- or 2.7-mm endoscope and to retain it at the apex of the arch, which can be moved in and out to visualize the entire transverse carpal ligament. The space below the blade is also used as a portal to insert scissors and instrumentation to cut the transverse carpal ligament. Results: All 8 carpal tunnels were completely released with no injury to the median nerve, superficial palmar arch, flexor tendon, or violation into Guyon canal. Mean distance of the flexor retinaculum division to the recurrent motor branch, palmar cutaneous branch, and superficial palmar arch was 6.87 ± 2.80, 7.13 ± 5.33, and 9.13 ± 4.42 mm, respectively. All specimens had an extraligamentous recurrent motor branch. Conclusions: The retractor and described technique were safe and effective in this cadaveric study. Further clinical trials are necessary before it can be adopted as a safe and reliable technique. Type of study/level of evidence: Therapeutic IV. © 2019 The Authors